Magnitude and correlates of internalised stigma among outpatient psychiatric service users in southeast central Ethiopia - Teklu Abraham; Teshome Kabeta; Yenealem Gezahegn (BMC Psychiatry)
Abstract Background Stigma is recognised as one of the most significant barriers to treatment for people with mental health conditions. However, limited studies are available in low-resource settings. Objectives To assess the magnitude of internalised stigma and associated factors among people with mental health conditions attending tertiary outpatient psychiatric services in Ethiopia. Methods A hospital-based cross-sectional study was conducted among 306 consecutively selected outpatient attendees of mental health services. Stigma was assessed using an interviewer administered instrument, the Internalised Stigma of Mental Illness Scale (ISMI) previously adapted for use in the Ethiopian setting. Data were collected using standard tools for medication adherence, social support, quality of life and self-esteem. Clinical information was extracted from medical record. Binary logistic regression analysis was carried out to assess factors associated with internalised stigma. Odds ratios along with 95% confidence intervals were estimated to measure the strength of the association. Results The magnitude of internalised stigma among participants was 36.6% [95% CI: (31.2%,42.3%)]. Having anxiety disorder [adjusted odds ratio (AOR) = 0.22; 95% confidence interval (CI): (0.07,0.66)], having other milder forms of psychiatric disorders [AOR = 0.19; 95% CI: (0.05,0.78)], a history of suicide attempt [AOR = 1.99; 95% CI: (1.02,3.87)], low self-esteem [AOR = 7.52; 95% CI: (3.58,15.78)] and poor quality of life [AOR = 2.06; 95% CI: (1.06,4.02)] were associated with internalised stigma among participants. Conclusion Internalised stigma remains a significant challenge among mental health service users in Ethiopia. Interventions that target individuals with psychotic, bipolar and depressive disorders with a history of suicide, low self-esteem and poor quality of life should be implemented to reduce internalised stigma among people with mental health conditions. Efforts should also target external factors, such as improving mental health literacy and challenging negative stereotypes.